Global e-Governance - Tubtimhin, Jirapon (IOS Press, 2013)
Governments are being transformed at every level due to advances in technology and innovative programs that open vast opportunities for delivery of public services, interact with citizens and business, and promote democracy. It is essential that those responsible for operating these services are well trained to provide the leadership needed for successful application of e-Services. This is the second volume in the Global e-Governance Series and focuses on Advancing e-Governance Through Innovation and Leadership by presenting original articles by international experts, National Case Studies and CIO Training Course materials. This book will serve as a research tool for those examining current economic developments, such as the financial crisis and how the consequences may impact the advancement of e-Government programs, including requirements for professional staff and experts to operate e-Services. Several chapters also address issues involved in promoting “Green ICT.” A number of potential benefits have been examined by several international organizations and national governments which could become a significant component. Consequently there are several practical dimensions to Advancing e-Government Through Innovation and Leadership.